Proceedings of 2011 International Conference for High Performance Computing, Networking, Storage and Analysis 2011
DOI: 10.1145/2063384.2063437
|View full text |Cite
|
Sign up to set email alerts
|

Optimized pre-copy live migration for memory intensive applications

Abstract: Abstract-Live migration is a widely used technique for resource consolidation and fault tolerance. KVM and Xen use iterative pre-copy approaches which work well in practice for commercial applications. In this paper, we study pre-copy live migration of MPI and OpenMP scientific applications running on KVM and present a detailed performance analysis of the migration process. We show that due to a high rate of memory changes, the current KVM rate control and target downtime heuristics do not cope well with HPC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 15 publications
(21 reference statements)
0
28
0
2
Order By: Relevance
“…The study indicated that our approach saves the total migration time by at least 65% and at most 75% in the memory intensive environment. This is in contrast to previous work in which, in the memory intensive environment, migration takes a long time or reaches a deadlock [6], [8]- [10]. In same environment, our approach can reduce more the total migration time compared to MECOM as much as 40%.…”
Section: Resultsmentioning
confidence: 61%
“…The study indicated that our approach saves the total migration time by at least 65% and at most 75% in the memory intensive environment. This is in contrast to previous work in which, in the memory intensive environment, migration takes a long time or reaches a deadlock [6], [8]- [10]. In same environment, our approach can reduce more the total migration time compared to MECOM as much as 40%.…”
Section: Resultsmentioning
confidence: 61%
“…Using network attached storage (NAS), downtime can be brought down to the order of milliseconds (Mian et al, 2011) but for a local persistent storage the downtime will be significantly higher. Migrating CPU state, migrating memory content (Ibrahim et al, 2011), migrating storage content (Hirofuchi et al, 2009a(Hirofuchi et al, , 2009b, and migrating network connections are the important steps to be followed in migrating a VM from source host do destination host. Clark et al (2011) proposed pre-copy migration technique.…”
Section: Literature Surveymentioning
confidence: 99%
“…As opposed to evacuation in the migratable-objects model, task migration in CoCheck was synchronous with the execution of the system, i.e., before an MPI rank could be migrated, CoCheck had to make sure all communicating ranks would hold back messages until the rank was at its new location. Similar tools have recently used process-level live migration in MPI applications [36], [37], [38]. Those tools combine health monitoring of nodes with live migration to provide proactive fault tolerance.…”
Section: Related Workmentioning
confidence: 99%